Severe acute respiratory distress syndrome in COVID-19 infected pregnancy: a case report - Undinti, Nagashree; R., Charumathi; Narasimhan, Rama; Alex, Neetu Mariam (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Corona virus 2019 is an emerging disease with a rapid increase in cases and deaths. Limited data is available about its progress and consequences in pregnancy. We present clinical challenges and potential strategies for optimal materno fetal surveillance by a case report on how we successfully managed a COVID -19 infected elderly primigravida with twin gestation and severe acute respiratory distress syndrome.